A insondável vida do lucumí Juan Nepomuceno Prieto - los Angeles, Maria de; Perera, Aisnara (Afro-Ásia, 2020)
Resenha de: LOVEJOY, Henry B.. Prieto: Yoruba Kingship in Colonial Cuba during the Age of Revolutions. Chapel Hill: University of North Carolina Press, 2018. 240p.